Semantic Matching Concept Using Semi-Automated Semantic Algorithm - Elangovan, D; Nirmala, K (International Journal of Computer Sciences and Engineering, 2019)
Semantic matching is a kind of ontology matching technique that depends on linguistics info encoded in light weight ontologies to establish nodes that square measure semantically connected. Ontologies matching are associate operator that identifies those nodes within the two structures that semantically correspond to at least one another. Matching concept is assessed into two classes like Syntax and linguistics Structures. Syntax matching concept is mainly focuses on syntax supported to the acceptable compiler. Linguistics is the main accustomed resolve the given word victimization logical analysis. The main objective of this proposed work is to determine the probability of semantic word used in the e-content which is retrieved from the given document. These techniques used to stem and trim the word from the given document and classify based on the knowledge such as Factual, Procedural and Conceptual. These Classified words are reconstructed into tree structures, used to calculate the probability of outcome and evidence. These effective and effusive techniques mainly to reduce the time, memory utilization and efficiency based on the proposed SAS (Semi-Automated Semantic) algorithm.